2019
DOI: 10.3390/dj7040115
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Peri-Implant Mucositis with Repeated Application of Chlorhexidine Chips or Gel during Supportive Therapy—A Randomized Clinical Trial

Abstract: Background: To assess the effect of chlorhexidine (CHX) chip application in patients with peri-implant mucositis as compared to CHX gel application. Methods: In peri-implant sites with mucositis, CHX gel was applied in the control group (GC) and CHX chips in the test group (CC) at baseline and after three months. At baseline and after six months, peri-implant pocket depths (PPD), bleeding-on-probing (BOP) and activated matrix metalloproteinase-8 (aMMP8) were assessed. Longitudinal changes were tested for inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Significant correlations have been found between aMMP-8 and progressing severity of periodontal and peri-implant diseases [ 3 , 4 , 6 , 7 , 26 ]. Successful periodontal and peri-implant treatment significantly reduces aMMP-8 levels in oral fluids [ 3 , 6 , 7 , 17 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant correlations have been found between aMMP-8 and progressing severity of periodontal and peri-implant diseases [ 3 , 4 , 6 , 7 , 26 ]. Successful periodontal and peri-implant treatment significantly reduces aMMP-8 levels in oral fluids [ 3 , 6 , 7 , 17 , 78 , 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ramseier et al reported a positive correlation between MMP-8, PI, and BOP in both GCF and PISF [ 65 ]. Ziebolz et al have demonstrated that PISF aMMP-8 levels can be kept successfully low during maintenance in patients undergoing successfully supportive implant therapy indicating that successful professional maintenance intervention is associated with low (<20 ng/ml) PISF aMMP-8 levels similar to the healthy peri-implant status [ 73 , 78 , 79 ]. Similar clinical parameters and MMP-8 levels were obtained with both zirconium and titanium abutments at the end of 1 year.…”
Section: Resultsmentioning
confidence: 99%
“…Dental water jet rinse mixed with chlorhexidine gel might supplement the response to nonsurgical treatment for peri-implantitis in a short term by reducing PPD [32]. Studies have found that repeated chlorhexidine chips application might resolve marginal peri-implant in ammation in terms of BOP better than chlorhexidine gel, and PPD was more reduced with 0.65 ± 0.40 mm [30,38]. The e cacy of a single dose is limited, repeated application of local drugs can prolong the effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Dental water jet rinse mixed with chlorhexidine gel might supplement the response to non-surgical treatment for periimplantitis lesions by reducing the PPD [32]. Some studies demonstrated that repeated application of chlorhexidine chips might resolve the marginal peri-implant inflammation in terms of BOP better than that by chlorhexidine gel, and the PPD was also reduced 0.65 ± 0.40 mm [30,38]. The efficacy of a single dose is limited, but the repeated application of local drugs can prolong the effectiveness.…”
Section: Discussionmentioning
confidence: 99%